O exército como família : etnografia sobre as vilas militares na fronteira - Silva, Cristina Rodrigues da (Universidade Federal de São Carlos, 2016)
This thesis is based on an ethnographic research on family dynamics in military villages located in the border region in the northwestern Amazon of Brazil. Our starting point considers the idea that the Brazilian Army seizes the "family" while native category which expresses the collective of the organization (the Military Family), prescribing relations to be modeled on solidarity and respect among its members (affections and moral duties that the military regard as “natural” behaviors of the family), which also extend to relations between their spouses/children and other military families, who perceive themselves as "relatives" in this universe (the physical proximity of these people within the villages - military sites - and the daily relations sharing would allow a family experience beyond consanguineous relationships). Through this, it is observed that the family is the object of constant care and it is sought to think the Army, on the one hand, doing and undoing familiarization through a system of standards and prescriptive behaviors (ideal model) which intervene in everyday relations of people who are part of this collective, and which aim to ensure the functioning of the military community as a family ruled by principles of hierarchy and discipline (structuring dimensions of the institution). On the other hand, the study explores, faced with this apparent uniformity of life in the barracks, how family members (especially the wives of officers and sergeants) think themselves in this system and also make and break family, stimulating a series of relationships within a conviviality in military towns, engaging in conflicts, gossiping and alliances. Throughout the thesis, therefore, we describe how both (institutions and individuals) flexibilize the family(ies), in order to produce other specific configurations of a military kinship.
Keywords: Família; Vila militar; Fronteira; Parentesco; Etnografia; Family; Military village; kinship; Border; Brazilian army; CIENCIAS HUMANAS::ANTROPOLOGIA